Improving Cognitive Learning Outcomes through the Implementation of a Culturally Responsive Teaching Approach at SMA Negeri 5 Banda Aceh - Emalfida; Mainisa; Hilma Astria (Indonesian Journal of Education and Social Humanities, 2025)
Today, learning is presented with various innovations that are according with the new paradigm, including in biology subject. The coordination system is one of complicated materials, so it requires an innovation that is oriented towards ethnopedagogy. This study aims to determine the increase in cognitive learning outcomes of class XI students through learning the coordination system using the Culturally Responsive Teaching (CRT) approach. The approach used in this study is a quantitative approach with the Classroom Action Research (CAR) type by using two learning cycles consisting of the stages of planning, implementing, observing and reflecting. This research was carried out by using test techniques in each cycle. Data analysis used a quantitative descriptive analysis which identified learning outcomes as class average scores and classical completeness percentages (KK). The results of the study showed that the CRT approach can improve student’s cognitive learning outcomes. This can be seen from the percentage of households in the first cycle of 88.9% and increased to 92.6% in the second cycle. Based on the results of this study it can be concluded that the CRT approach is able to improve cognitive learning outcomes of students in class XI SMAN 5 Banda Aceh.